HUBUNGAN ANTARA RELIGIUSITAS DAN REGULASI EMOSI DENGAN PERILAKU PROSOSIAL PADA REMAJA DI SMK KETINTANG SURABAYA - Silfiyah, Khoirotus (Universitas Nahdlatul Ulama Sunan Giri, 2019)
This study aims to know the relationship between religiosity and emotional regulation towards prosocial behavior in adolescents. The subject of the study is 107 adolescents from SMK Ketintang Surabaya, ranging between the ages of 15-18 years old. Using regression analysis, the result shows the existence of relationship between religiosity, emotional regulation, and prosocial behavior (Freg = 36.108; p = 0.001 < 0.01); and also of positive relationship between religiosity towards prosocial behavior (t reg = 5.561; p = 0.001 < 0.01); as well as the positive relationship between emotional regulation towards prosocial behavior (t reg = 2.348; p = 0.021 < 0.05).